Shadowing as peer experiential learning for faculty instructional development strategy: A case study on a computer science course - Rodolfo M. Vega (Elsevier, 2021)
Shadowing as an approach for getting first-hand learning experiences and in gathering information about workplace practices and performances has been widely used in different fields. In this case study, we analyze and propose a shadowing strategy that uses ethnographic methods for experiential learning that serves the purpose of gaining experience by learning from and playing the same role as the person being shadowed. The experiential learning process has been performed by shadowing a professor in a graduate course in Carnegie Mellon University. The use of ethnographic methods in shadowing has allowed the learner (the shadower), to elicit the knowledge and learn while the person being shadowed performs as teacher and mentor. The uniqueness of the shadowing methodology that we propose and use in this experience is the combination of experiential learning and ethnographic research methods for an in-depth analysis of the learning experience. Another uniqueness is that shadowing is based on interactions between the shadower and shadowee as peers, both being university professors in the field of computer science, where the shadowee acts as mentor. We propose this approach of faculty shadowing as a method for faculty development in higher education pedagogy.